Bridging the Digital Divide: Fostering STEM Education for Digital Economy Leadership - James Maisiri; Takaedza Simbarashe Madzikanda (Journal of BRICS Studies)
As BRICS countries strive to build a digital economy, these nations must prepare their populous for the ‘future of work.’ Digital economies tend to create middle to high-skilled jobs. This is problematic as many workers are trapped in low-skill occupations and lack the expertise to participate in a digital economy adequately. A digital economy requires a population that is literate in Science, Technology, Engineering, and mathematics (STEM). While BRICS has made progress in educating their populous in these fields, they still have a long way to go. More STEM graduates (especially women) must be produced to maintain and create a digital economy. This policy brief maps out strategies for BRICS countries to increase STEM participation.